Mengurai Dampak Penggunaan Gadget pada Tumbuh Kembang Anak Usia Dini: Perspektif Kesehatan dan Pendidikan di PAUD Al Barokah - Hidayat, Amat; Nasrullah, Anton; Rizkiyah, Siti; Ernawati, Ernawati; Fauziah, Eva; Mulhanah, Mulhanah; Supartini, Siti; Mu'minah, Mu'minah; Aisah, Siti; Muliani, Yeni Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
The use of gadgets among early childhood is increasing along with technological developments. Gadgets provide various conveniences, but excessive use can have a negative impact on children's growth and development, especially in terms of health and education. This service aims to educate parents and teachers at PAUD Al Barokah about the impact of gadget use on early childhood and provide strategies to minimize its negative impacts. The method used is counseling with a participatory approach through discussion and training. The results of the service show an increase in participants' knowledge regarding managing gadget use time and implementing healthier activities to support optimal child development. In conclusion, early childhood education and health can be protected by limiting gadget use and replacing it with more interactive and physical activities.